Analyses of Factors Affecting Endothelial Cell Density in an Eye Bank Corneal Donor Database. Issue 9 (September 2016) - Kwon, Ji Won; Cho, Kyong Jin; Kim, Hong Kyu; Lee, Jimmy K.; Gore, Patrick K.; McCartney, Mitchell D.; Chuck, Roy S.
Abstract : Purpose: To analyze the factors affecting central corneal endothelial cell density (ECD) in an eye bank corneal donor database. Methods: The Lion's Eye Institute corneal donor database consisting of 18, 665 donors (34, 234 corneas) aged 20 years or older was analyzed. In particular, differences in the ECD based on age, sex, race, prior ocular surgery, a history of systemic diseases, and smoking were investigated. Furthermore, risk factors for donor cell count inadequacy (defined here as ECD less than 2000/mm 2 ) were identified. Results: ECD decreased with age. Regarding race, the average ECD of African American donors was higher than those of white or Hispanic donors. A history of diabetes mellitus (DM) and ocular surgery were associated with a lower ECD. Donor medical history of hypertension, glaucoma, depression, dementia, Parkinson disease, hyper- or hypothyroidism, or smoking did not seem to affect the ECD. The risk factors for donor cell count inadequacy, based on binary logistic regression analyses were advanced age [65–74 years yielded an odds ratio of 17.8; confidence interval (CI), 10.6–29.8; P < 0.001; and 75–99 years yielded an odds ratio of 24.6 (CI, 14.5–41.61; P < 0.001) when compared with 20–34 years], cataract surgery (odds ratio, 4.3; CI, 4.0–4.8; P < 0.001), and DM (odds ratio, 1.2; CI, 1.1–1.3; P = 0.001). Conclusions: Age, race, ocular surgery (cataract and refractive), and DM seem to significantly affect donor corneal ECD. Of these variables, age, a history of cataract surgery, and DM were found to be the greatest risk factors for inadequate donor cell density (less than 2000/mm 2 ).